Analysis of the Load Sharing Behaviour and Cushion Failure Mode for a Disconnected Piled Raft - Xiao-jun Zhu (Advances in Materials Science and Engineering)
Disconnected piled raft (DPR) foundations are characterized by having no structural connection to a raft. The raft-pile gap is filled with a granular cushion, which creates a more uniform pressure distribution on the raft and reduces the differential settlement. A series of tests has been performed to investigate the load transfer mechanisms of a DPR. The effects of the thickness and stiffness of the cushion and the pile diameter are presented and discussed. A simple failure mode of the cushion is also put forward according to the cushion slip plane obtained by using the digital image correlation technique that tracks the pixels in the images and generates a displacement field. Then a new theoretical analysis has been presented for rigid pile composite foundation. Through comparative studies, it is found that the present method is validated as reasonable by laboratory tests and is in agreement with several current design methods.